Penggunaan Model Pembelajaran Everyone Is A Teacher Berbasis Peta Konsep Terhadap Hasil Belajar Fisika SMP - Muqarrobin, Tamman Firdaus (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2022)
This study aims to determine the results of learning Physics for students who are given the everyone is a teacher learning model on Newton's Law material at SMP 4 Widodaren. The research sample was 120 grade VIII students of SMP 4 Widodaren. The researcher divided into two classes, namely the first VIII as a control class with 60 students and the second VIII as an experimental class with 60 students. The research used was the Two Group Pretest-Posttest Design. The analysis technique used is descriptive analysis and t-test. Based on the analysis tcount = 2.928 > ttable = 2.069 and Y = 49.64 + 0.412X In this equation the linear regression direction coefficient (b) = 0.412 is positive, meaning that student learning outcomes in learning physics in Newton's Law material can improve using the Everyone Learning model is a teacher.